Water productivity and agronomic performance of strawberries with different leaching fractions application - Gontijo, Mariana Lúcio; Souza, Fabiana Silva; Diotto, Adriano Valentim; Souza, Fabiana Silva de; Gontijo, Fernanda Lúcio (Scientia Plena, 2020)
Strawberry is an economically important crop. However, because this crop is very susceptible to pests and diseases, the use of new management techniques, such as semi-hydroponic cultivation, is necessary. One of the greatest difficulties for producers in the transition from soil to semi-hydroponic cultivation is fertigation management. As most crops in Brazil are grown in open fields, monitoring the electrical conductivity of the drained solution is key. Thus, the aim of this study was to use different leaching fractions to evaluate the control of saline levels and the productivity of the San Andreas strawberry. The experimental design was completely randomized. The treatments consisted of different leaching fractions, equivalent to 10, 20, 30, and 50% excess irrigation. Most of the evaluated traits were significantly affected at the 5% level of significance according to Tukey’s test. The 30% leaching fraction showed the best results in practically all evaluations, with better values obtained even for water productivity and with 19.92 g of fruit per liter of solution used.